2018 ACC/HRS/NASCI/SCAI/SCCT Expert Consensus Document on Optimal Use of Ionizing Radiation in Cardiovascular Imaging—Best Practices for Safety and Effectiveness, Part 1: Radiation Physics and Radiation Biology: A Report of the American College of Cardiology Task Force on Expert Consensus Decision Pathways Developed in Collaboration With Mended Hearts. Issue 2 (29th August 2018) - ,; Hirshfeld, John W.; Ferrari, Victor A.; Bengel, Frank M.; Bergersen, Lisa; Chambers, Charles E.; Einstein, Andrew J.; Eisenberg, Mark J.; Fogel, Mark A.; Gerber, Thomas C.; Haines, David E.; Laskey, Warren K.; et al.
Abstract: The stimulus to create this document was the recognition that ionizing radiation‐guided cardiovascular procedures are being performed with increasing frequency, leading to greater patient radiation exposure and, potentially, to greater exposure for clinical personnel. Although the clinical benefit of these procedures is substantial, there is concern about the implications of medical radiation exposure. The American College of Cardiology leadership concluded that it is important to provide practitioners with an educational resource that assembles and interprets the current radiation knowledge base relevant to cardiovascular procedures. By applying this knowledge base, cardiovascular practitioners will be able to select procedures optimally, and minimize radiation exposure to patients and to clinical personnel. Optimal Use of Ionizing Radiation in Cardiovascular Imaging: Best Practices for Safety and Effectiveness is a comprehensive overview of ionizing radiation use in cardiovascular procedures and is published online. To provide the most value to our members, we divided the print version of this document into 2 focused parts. Part I: Radiation Physics and Radiation Biology addresses the issue of medical radiation exposure, the basics of radiation physics and dosimetry, and the basics of radiation biology and radiation‐induced adverse effects. Part II: Radiological Equipment Operation, Dose‐Sparing Methodologies, Patient and Medical Personnel Protection covers the basics of operation and radiation delivery for the 3 cardiovascular imaging modalities (x‐ray fluoroscopy, x‐ray computed tomography, and nuclear scintigraphy) and will be published in the next issue of the Journal .